Evaluation and Analysis of Indicators of the Creative City in Metropolises: Case Study of District 1 of Tabriz Metropolis - majid dadashpour mghadam; Reza Valizadeh (نشریه جغرافیا و برنامه‌ریزی, 2020)
Introduction Cities are the wealth centers in every country. However, the nature of wealth production and development has changed in the current century. The new concept of wealth production is based on creation of an idea and converting that into production and service. This issue is more expanded in metropolises. In today’s world, metropolises play a significant role in formation of the economic, social, cultural, political, and technological flows; so that, they have become the focus of dynamism, creativity, production, and economic and social development of the world. The today’s metropolises are considered the centers of creativity, wealth, power, mass production, cultural innovations, different types of ideology, and also mass consumption. Due to their properties such as concentration, diversity, and dynamism, the cities have the potential of educating and attracting creative human capitals and achieving the economic development. The Iranian metropolises have also a wide variety of services and facilities, and this is their distinctive characteristic. Furthermore, the variety of economic activity, the concentration of the majority of educational centers and technological activities, information generation, existence of the main cultural centers, etc. can attract the creative capitals and provide the opportunity of affording a relative welfare. Creative economic, creative industries, creative class, and in general creative city play a significant role in the economic, social, and cultural development and regeneration of the urban space. So, the present research aims to investigate the indicators of creative city in Tabriz metropolis; because metropolises are faced with different problems, and they need to adopt creativity for solving their social and economic problems. According to Peter Hall, creative cities are the cities having a mixed sociocultural context that provides the opportunity of more interaction and an easier information exchange among the creative people. This condition leads to creation of new ideas and creative thinking. Others believe that creative cities are characterized by acceptance of different social, ethnic, and cultural groups, the ability to solve the civil problems, creation of an environment attracting the creative and innovative persons, promotion of creativity, and applying the residents’ opinions to solve the problems and achieve economic growth and development. A creative city is characterized by different criteria such as creative human capital, creative class, diversity, openness, research and development, participation, innovative technology, employment, entrepreneurship, infrastructures, brand, etc. A creative city provides a context in which, the managers and planners investigate the urban problems creatively and based on the collective thinking of the main owners of the urban space i.e. the citizens and business owners. In such an environment, the stakeholders and the authorities work with each other to solve the problems existing in the cities and improve the living conditions in urban environments. This activity results in promoted quality of the urban environment and increased livability of the city. The main assumption of a creative city is that the general public can perform extraordinary tasks, provided that they have the required opportunity. The research goals include the following: -          Evaluation of the participation indexes of creative city in District 1 of Tabriz – Evaluation of capital attraction index in District 1 of Tabriz -          Evaluation of urban space diversity in District 1 of Tabriz – Evaluation of knowledge- based technology in District 1 of Tabriz Methodology This research is an applied study performed by a descriptive-analytical approach. Data collection has been done by library resources and field studies. Results  and discussion The present research has investigated four variables, including participation, urban space diversity, capital attraction, and communication technologies in District 1 of Tabriz metropolis. As the fifth metropolis of the country, Tabriz has ten regions the largest of which is the District 6 and the smallest is the District 8. In terms of population, District 4 has the highest population and District 2 has the lowest population. The increasing population growth in Tabriz metropolis, especially in its suburbs i.e. District 1, and the low-income residents of this region, it is necessary to evaluate the creative city indicators in District 1 of Tabriz metropolis. Regarding the importance of this issue, the present research aims to analyze the creative city indicators in metropolises as a case study performed in District 1 of Tabriz metropolis. The results showed that District 1 of Tabriz metropolis is faced with various problems in terms of the creative city indicators. District 1 of Tabriz has dealt with many problems due to the excessive migrations, the increasing growth of the urban population, the changes in urban development, the variety of subcultures, and lack of dynamism and viability. The instability of different regions of Tabriz has been manifested in different problems such as social abnormalities, lack of public participation, the increased costs of urban management, lack of vitality and viability in the citizens, etc. Conclusion As a result of evaluating the creative city indicators in District 1 of Tabriz, the worst and the best situations of the variables in every index were respectively reported as the following: urban administration (with the mean value of 1.98) and public participation in proposing new ideas (2.16) in the participation index, architectural diversity (2.64) and existence of welfare, commercial, and sports centers (3.24) in the urban space diversity index, foreign capital attraction (2.27) and domestic capital attraction (3.144) in the capital attraction index, access to service and communication centers (2.79) and ATM access (3.60) in the communication technology index. In general, there was a significant direct relationship between the components of participation, urban space diversity, capital attraction, communication technology, and creative environment in District 1 of Tabriz.